Selenium toxicity stress-induced phenotypical, biochemical and physiological responses in rice plants: Characterization of symptoms and plant metabolic adjustment - Cabral Gouveia, Geraldo Candido [UNESP]; Galindo, Fernando Shintate [UNESP]; Dantas Bereta Lanza, Maria Gabriela [UNESP]; Caroline da Rocha Silva, Anne [UNESP]; Pereira de Brito Mateus, Matheus [UNESP]; Souza da Silva, Marcio [UNESP]; Rimoldi Tavanti, Renan Francisco [UNESP]; Tavanti, Tauan Rimoldi [UNESP]; Lavres, José; Reis, André Rodrigues dos [UNESP] (Elsevier, 2020)
Selenium (Se) at low concentration is considered benefit element to plants. The range between optimal and toxic concentration of Se is narrow and varies among plant species. This study aimed to evaluate the phenotypic, physiological and biochemical responses of four rice genotypes (BRS Esmeralda, BRSMG Relâmpago, BRS Bonança and Bico Ganga) grown hydroponically treated with sodium selenate (1.5 mM L−1). Selenium treated plants showed a dramatically decrease of soluble proteins, chlorophylls, and carotenoids concentration, resulting in the visual symptoms of toxicity characterized as leaf chlorosis and necrosis. Selenium toxicity caused a decrease on shoot and root dry weight of rice plants. Excess Se increased the oxidative stress monitored by the levels of hydrogen peroxide and lipid peroxidation. The enzymatic antioxidant system (catalase, superoxide dismutase, and ascorbate peroxidase) increased in response to Se supply. Interestingly, primary metabolism compounds such as sucrose, total sugars, nitrate, ammonia and amino acids increased in Se-treated plants. The increase in these metabolites may indicate a defense mechanism for the osmotic readjustment of rice plants to mitigate the toxicity caused by Se. However, these metabolites were not effective to minimize the damages on phenotypic traits such as leaf chlorosis and reduced shoot and root dry weight in response to excess Se. Increased sugars profile combined with antioxidant enzymes activities can be an effective biomarkers to indicate stress induced by Se in rice plants. This study shows the physiological attributes that must be taken into account for success in the sustainable cultivation of rice in environments containing excess Se.
Keywords: Amino acids; Genotypic variation; Oryza sativa L.; Phytotoxicity; Primary metabolism; Selenium